EPR-Spin Trapping and Flow Cytometric Studies of Free Radicals Generated Using Cold Atmospheric Argon Plasma and X-Ray Irradiation in Aqueous Solutions and Intracellular Milieu - Uchiyama, Hidefumi; Zhao, Qing-Li; Hassan, Mariame Ali; Andocs, Gabor; Nojima, Nobuyuki; Takeda, Keigo; Ishikawa, Kenji; Hori, Masaru; Kondo, Takashi (PLOS ONE, 2015)
Electron paramagnetic resonance (EPR)-spin trapping and flow cytometry were used to identify free radicals generated using argon-cold atmospheric plasma (Ar-CAP) in aqueous solutions and intracellularly in comparison with those generated by X-irradiation. Ar-CAP was generated using a high-voltage power supply unit with low-frequency excitation. The characteristics of Ar-CAP were estimated by vacuum UV absorption and emission spectra measurements. Hydroxyl (·OH) radicals and hydrogen (H) atoms in aqueous solutions were identified with the spin traps 5,5-dimethyl-1-pyrroline N-oxide (DMPO), 3,3,5,5-tetramethyl-1-pyrroline-N-oxide (M4PO), and phenyl N-t-butylnitrone (PBN). The occurrence of Ar-CAP-induced pyrolysis was evaluated using the spin trap 3,5-dibromo-4-nitrosobenzene sulfonate (DBNBS) in aqueous solutions of DNA constituents, sodium acetate, and L-alanine. Human lymphoma U937 cells were used to study intracellular oxidative stress using five fluorescent probes with different affinities to a number of reactive species. The analysis and quantification of EPR spectra revealed the formation of enormous amounts of ·OH radicals using Ar-CAP compared with that by X-irradiation. Very small amounts of H atoms were detected whereas nitric oxide was not found. The formation of ·OH radicals depended on the type of rare gas used and the yield correlated inversely with ionization energy in the order of krypton > argon = neon > helium. No pyrolysis radicals were detected in aqueous solutions exposed to Ar-CAP. Intracellularly, ·OH, H2O2, which is the recombination product of ·OH, and OCl- were the most likely formed reactive oxygen species after exposure to Ar-CAP. Intracellularly, there was no practical evidence for the formation of NO whereas very small amounts of superoxides were formed. Despite the superiority of Ar-CAP in forming ·OH radicals, the exposure to X-rays proved more lethal. The mechanism of free radical formation in aqueous solutions and an intracellular milieu is discussed.